Education Policy on Operational Assistance Management at the Local Level: A Challenge and Recommendations - Agus, Andi; Hakim, Lukman; Mahsyar, Abdul; Fatmawati (International Journal of Science and Society, 2024)
This research discusses the Implementation Operational Assistance Program (BOP) at the local level as a fund management mechanism to support educational activities in schools, provide equitable access to education, encourage educational inclusion, and reduce disparities between regions. This study uses a qualitative approach with a focus on thematic analysis. This approach was chosen to guide researchers to find sources of analysis directly from the government by identifying several official government documents. This study's findings indicate several challenges in managing BOP locally, such as a need for more resources, infrastructure and technical capabilities. Several policy recommendations are suggested to overcome these challenges, namely by increasing monitoring and evaluation, transparency, management capacity, use of technology, and collaboration. With the implementation of the right policies, BOP management at the local level can be improved so that education can become a more inclusive, quality and sustainable means for all parties.